Luis de Valdivia: esbozos de un diálogo intercultural e interreligioso en el contexto de la Guerra de Arauco - Sepúlveda del Río, Ignacio (Cauriensia, 2023)
In the context of the Arauco War, at the end of the 16th century and the beginning of the 17th century, the Grenadian Jesuit Luis de Valdivia proposed the Defensive War between the Spanish Crown and the Mapuche people. The Defensive War implies, on the one hand, the recognition of a physical frontier, but it also means the recognition to the indigenous people of their own freedom and way of life. In this situation, an outline of intercultural and interreligious dialogue is generated between Spaniards and Mapuche that will forge, through time, processes of acculturation and inculturation. This paper seeks to show the lights and shadows of this dialogue both through the Defensive War and in the search for the evangelization of the Mapuche people.